PENGARUH TERAPI BEKAM KERING TERHADAP PENURUNAN SKALA NYERI PADA PASIEN DENGAN NYERI GASTRITIS DI KLINIK PERAWAT LATU HUSADHA ABIANSEMAL BADUNG - Kristina, Ita (Coping: Community of Publishing in Nursing; Vol 2 No 1 (2014): JURNAL EDISI JANUARI-APRIL 2014, 2014)
Gastritis is a digestive health problems most frequently occur. Approximately 10% of people who come to the emergency room on physical examination found tenderness in the epigastric region. Of data that can be in the Bali Provincial Health Office showed that Gastritis is included in the top 10 Great Disease in Outpatient Health Center in 2011 and found of gastritis cases as 1133 cases a year. Prominent complaint in patients with gastritis is the pain in epigastric. Various attempts were made by patients to relieve is gastritis pain. Efforts to use the drugs (pharmacology) or without the use of drugs (non-pharmacological). One example of complementary therapies (Complementary Medicine) which is used for pain that is dry cupping therapy. The purpose of this study was to determine the effect of dry cupping therapy to decrease pain scale in patients with gastritis pain. The study was conducted from March to April 2013, the pre-experimental research design with the design of a one-group pretest-posttest design. Sampling using non-probability sampling technique (purposive sampling). The sample in this study amounted to 73 people. Researchers measured patients' pain scale using a numerical pain scale before dry cupping therapy given as a pre-test phase, and after being given a dry cupping therapy for ± 20 minutes as a post test. Kolmogorov Smirnov analysis showed the value of p = 0.000 (p <0.05), which means the data is not normally distributed. Because the data in this study are not normally distributed, then the analysis is the analysis of non parameterik Wilcoxon test, p = 0.000 (p <0.05), which means that Ho is rejected or in other words, there is the influence of dry cupping therapy to decrease the scale pain in patients with gastritis pain. Given that dry cupping therapy is effective in reducing pain scale in patients with gastritis pain, it is expected that this therapy can be used in a particular non-pharmacological treatment for pain.
Keywords: Pain, Gastritis, Dry cupping